Security in the new world order : an Indo-French dialogue - Banerjee, Dipankar; Institute for Defence Studies and Analyses; Fondation nationale des sciences politiques. Centre d'etudes et de recherches internationales (New Delhi : Institute for Defence Studies and Analyses, 1994)
Papers presented at a colloquium between Institute for Defence Studies and Analyses and Centre d'etudes et de recherches internationales, Fondation nationale des sciences politiques, at New Delhi, Dec. 1994.
Includes bibliographical references.
Keywords: Securities, International -- Congresses; Nuclear nonproliferation -- Congresses; Post-communism -- Communist countries -- Congresses; World politics -- 1989- -- Congresses; National security -- South Asia -- Congresses; India -- Foreign relations -- France -- Congresses; France -- Foreign relations -- India -- Congresses